MHD viscoelastic nanofluid flow across an extended plate using mixed convection and thermal radiation - Mukhtar, Safyan; Rana, Siddra; Mansoor, Muavia; Arooj, Tayyaba; Ul Hassan, Qazi Mahmood; Shah, Rasool (Frontiers in Energy Research, 2024)
Opportunities for magneto-hydrodynamic mixed convection include modelling firefighting, combustion engineering, and the cooling of electronic components. Nanotechnology has just provided a novel passive technique for improving heat transfer. Structured colloidal suspensions of magnetite nanoparticles in a base fluid are known as magneto nanofluids, and they are intended for use in thermal transfer uses, such as micro device cooling mechanisms. The current model is intended for examination of the nanofluid stagnation point flow using magneto hydrodynamics. A stretched sheet was exposed to magnetic strength and thermal radiation effects with outstanding results on heat transfer enhancements under mixed convection conditions. Furthermore, over the boundary effects of thermal slip and velocity are considered. Persuading system of partial differential equations of governed fluid model are transformed into a scheme of coupled nonlinear ordinary differential equations, and expounded using suitable numerical method. The fluid's velocity, temperature, and concentration of nano particles are discussed graphically for a range of newly emerging parametric values. It has been noted that when there is a magnetic field, the fluid's temperature rises but its velocity decreases. After obtaining the numerical solution, parameters characterizing the flow, such as the local skin friction coefficient, local Sherwood number, and local Nusselt number, are thoroughly investigated.